India's democracies Diversity, Co-optation, Resistance - Engelsen Ruud, Arild; Heierstad, Geir (Universiteitsforlaget, 2016)
This volume is about India's deep and complex relationship with its chosen form of government. It is an interdisciplinary book with approaches drawn from history, anthropology, sociology, political science and social geography. We believe this volume provides new perspectives on how to approach and analyse the complexity of India's democracy. The book's unfortunate publishing history also tells a tale of India.